Deconstruction of Lignocellulose into Soluble Sugars by Native and Designer Cellulosomes - Sarah Moraïs (American Society for Microbiology, 2012)
ABSTRACT Lignocellulosic biomass, the most abundant polymer on Earth, is typically composed of three major constituents: cellulose, hemicellulose, and lignin. The crystallinity of cellulose, hydrophobicity of lignin, and encapsulation of cellulose by the lignin-hemicellulose matrix are three major factors that contribute to the observed recalcitrance of lignocellulose. By means of designer cellulosome technology, we can overcome the recalcitrant properties of lignocellulosic substrates and thus increase the level of native enzymatic degradation. In this context, we have integrated six dockerin-bearing cellulases and xylanases from the highly cellulolytic bacterium, Thermobifida fusca, into a chimeric scaffoldin engineered to bear a cellulose-binding module and the appropriate matching cohesin modules. The resultant hexavalent designer cellulosome represents the most elaborate artificial enzyme composite yet constructed, and the fully functional complex achieved enhanced levels (up to 1.6-fold) of degradation of untreated wheat straw compared to those of the wild-type free enzymes. The action of these designer cellulosomes on wheat straw was 33 to 42% as efficient as the natural cellulosomes of Clostridium thermocellum. In contrast, the reduction of substrate complexity by chemical or biological pretreatment of the substrate removed the advantage of the designer cellulosomes, as the free enzymes displayed higher levels of activity, indicating that enzyme proximity between these selected enzymes was less significant on pretreated substrates. Pretreatment of the substrate caused an increase in activity for all the systems, and the native cellulosome completely converted the substrate into soluble saccharides. IMPORTANCE Cellulosic biomass is a potential alternative resource which could satisfy future demands of transportation fuel. However, overcoming the natural lignocellulose recalcitrance remains challenging. Current research and development efforts have concentrated on the efficient cellulose-degrading strategies of cellulosome-producing anaerobic bacteria. Cellulosomes are multienzyme complexes capable of converting the plant cell wall polysaccharides into soluble sugar products en route to biofuels as an alternative to fossil fuels. Using a designer cellulosome approach, we have constructed the largest form of homogeneous artificial cellulosomes reported to date, which bear a total of six different cellulases and xylanases from the highly cellulolytic bacterium Thermobifida fusca. These designer cellulosomes were comparable in size to natural cellulosomes and displayed enhanced synergistic activities compared to their free wild-type enzyme counterparts. Future efforts should be invested to improve these processes to approach or surpass the efficiency of natural cellulosomes for cost-effective production of biofuels.